Metáforas conceptuais no discurso docente: revelando práticas - Andrade, Luiz Henrique Santos de (2011)
The present work aims to describe the metaphorical linguistic expressions and their conceptual metaphors, recurrent in the lesson discursive genre. The hypothesis that guides this research is that the conceptual metaphors are present in the speech of Portuguese Language teachers through the linguistic expressions, which reveal the language conception that supports their pedagogical practice. To prove this hypothesis we used as theoretical reference the following theories: The Theory of Conceptual Metaphor and Language Conceptions postulated by Linguistics. The corpus of our research consists of twelve lessons of Portuguese Language, six lessons were recorded in elementary school and the others in high school, during September, October and November in 2009. The results not only confirmed the hypothesis, as they pointed out that most teachers say that adopt the perspective of language as a place of human interaction, but we perceived that the lessons are still worked in a traditional way.